Concentrations of organochlorine compounds (pesticides and PCBs), trace elements (Pb, Cd, Cu, and Hg), Cs-134, and Cs-137 in the livers of the European otter (Lutra lutra), great cormorant (Phalacrocorax carbo), and European catfish (Silurus glanis), collected from the Loire River (France) - Alomar, Hussein; Lemarchand, Charles; Rosoux, Rene; Vey, Daniele; Berny, Philippe (European Journal of Wildlife Research, 2016)
In this study, liver samples of the European otter (Lutra lutra), great cormorant (Phalacrocorax carbo), and European catfish (Silurus glanis) from along the Loire River (France) were analyzed for organochlorine pesticides, polychlorinated biphenyls (PCBs), trace elements (lead, cadmium, copper, and mercury), Cs-134, and Cs-137. Organochlorine compounds were found in 100 % of the samples. Residue level of PCBs in these predators was the highest followed by DDTs and endosulfan, and maximal PCB values reached 1.61, 1.96, and 0.28 mg/kg wet weight for cormorants, otters, and catfish, respectively. DDTs, endosulfan, and lindane were the abundant pesticides in the livers of these predators. Concentrations of copper, lead, and cadmium in the livers of top predators were generally low; a potentially toxic level of lead was found in only one cormorant (34.9 mg/kg dry weight). Mean mercury concentrations in cormorant, otter, and catfish livers were 5.47, 4.68, and 2.71 mg/kg dry weight, respectively, and exceeded toxic thresholds for more than 40 % of the cormorants. Levels of organochlorine compounds and trace elements in these predators are generally below known toxic thresholds, but potential combined effects are not studied and warrant more investigations.